(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2017)
The aim of the current paper is to take an analytical approach to the diverse factors, educational, theological, cultural and political, which might have played a role in historically shaping the identity and, hence, the nature of Seventh-day Adventist spirituality as to its commitment to generally applicable civic freedom of conscience. The research has evidenced that denominational activism for the defence of the fundamental political rights of the individual to religious freedom had evolved into a new feature of Adventist spirituality from 1884 onwards. It was in this year that the Sabbath Sentinel was launched, the name of which came to be changed to American Sentinel of Religious Liberty in 1886. This was known as the official organ of the Seventh-day Adventist Church to represent the ideal of liberty of conscience and that of the free practice of faith for all citizens irrespective of their religious commitments.